Impact of Cycling on Mental Health and Self-Esteem in The Elderly - Heru Herdiana Nugraha; Nurlan Kusmaedi; Yusup Hidayat; Hasanul Fitrah Alba (Universitas PGRI Palembang, 2022)
The elderly are an age group that is vulnerable to changes due to the aging process and these changes cause problems that can affect the quality of life of the elderly. This study aims to find out the impact of cycling activities on mental health and self-esteem in the elderly. Metode research used in this study method Causal-comparative research (Expost-Facto). The design used in this study is criterion-groupdesign. This research uses sampling techniques using non probability sampling,i.e. by purposive sampling. The sample in this study amounted to 40 people divided into 2 groups between the elderly who were active cycling and the elderly who were not active in sports. This study used two measuring instruments in the form of questionnaires, namely Depression Anxiety Stress Scale 42 (WATERSHED 42) and Self-Esteem Rating Scale (SERS). Data analysis is processed using SPSS software version 25. The results showed that there were differences in mental health and self-esteem between elderly people who were actively cycling and the elderly who were not active in sports judging from the t-test with Sig. (2 Tailed< 0.05 by drawing Sig conclusions. (2-tailed) mental health by 0,000 < 0.05 and self-esteem by 0.000 < 0.05. That is, cycling activities have an impact on the mental health and self-esteem of the elderly.